The Dissolving Ability of Different Organic Solvents on Three Different Root Canal Sealers: In Vitro Study - mushtaq, mubashir; masoodi, ajaz; farooq, riyaz; khan, fayiza (Iranian Endodontic Journal, 2012)
Introduction: The purpose of this in vitro study was to evaluate three common gutta-percha solvents’ effectiveness in dissolving three different types of root canal sealers. Materials and Methods: The solubility of three different root canal sealers (AH Plus, Apexit Plus and Endoflas FS) was assessed in xylene, refined orange oil, tetrachloroethylene and distilled water (control). One-hundred twenty samples of root canal sealers were prepared and then divided into three equal groups (n=40). Each group was further divided into four equal subgroups (n=10) for immersion in the respective solvents for a 10 minute immersion period. The mean amount of weight loss was determined for each material in each solvent during the specified immersion period, and the values were subjected to statistical analysis. <span style="font-style: normal; font-family: "Times New Roman","serif"; color: black; font-size: 11pt; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: Arial; mso-fareast-language: ZH-CN; mso-bidi-language: FA;">Results: Xylene exhibited the greatest dissolving efficacy for AH Plus, followed by refined orange oil and tetrachloroethylene. Xylene was also able to dissolve the greatest amount of Apexit Plus, followed by refined orange oil and tetrachloroethylene which were equally effective in dissolving Apexit Plus. For Endoflas FS, maximum dissolving efficacy was seen with tetrachloroethylene followed by refined orange oil and xylene. <span style="font-style: normal; font-family: "Times New Roman","serif"; color: black; font-size: 11pt; mso-fareast-font-family: ’Times New Roman’; mso-fareast-language: ZH-CN; mso-bidi-language: FA; mso-ansi-language: EN-US;">Conclusion<span style="font-style: normal; font-family: "Times New Roman","serif"; color: black; font-size: 11pt; mso-fareast-font-family: ’Times New Roman’; mso-fareast-language: ZH-CN; mso-bidi-language: FA; mso-ansi-language: EN-US;">: <span style="font-family: "Times New Roman","serif"; color: black; font-size: 10pt; mso-fareast-font-family: Calibri; mso-bidi-font-family: Arial; mso-fareast-language: EN-IN; mso-bidi-language: AR-SA; mso-ansi-language: EN-US;">The results showed that xylene, refined orange oil and tetrachloroethylene can be used for the removal of AH Plus, Apexit plus and Endoflas FS sealers during endodontic retreatment. Further clinical investigations are needed to evaluate the efficacy of these solvents on different sealers.